Effect of shade and various types of animal manure fertilizer on the yield of shallot (Allium ascalonicum L.) Lokananta variety of true shallot seed (TSS) in Ultisol soil - Indra Jaya; Eries Dyah Mustikarini; Tri Lestari (Universitas Trunojoyo Madura, 2026)
Shallot is an important horticultural commodity. Shallotproduction is influenced by variety, planting material, environment,growing media, and nutrient availability. Optimal sunlight intensityand appropriate nutrient types are essential to achieve high yields.Adequate nutrients can be obtained through the application ofanimal manure to the growing media. This study aimed to determinethe effect of shading and types of animal manure on the yield ofLokananta shallot variety from True Shallot Seed (TSS) grown inUltisol soil. The research was conducted on Ultisol soil inPangkalpinang City, Bangka Belitung Islands Province, from April toSeptember 2024. A split-plot design arranged in a RandomizedComplete Block Design (RCBD) was used. The main plot was shadingtreatment (with shading and without shading), and the subplot wastypes of animal manure (chicken, cattle, goat, swiftlet, and batmanure). Data were analyzed using Fisher's test and the HonestlySignificant Difference (HSD) test at a 95% confidence level. Theresults showed that the treatment without shading produced the bestagronomic characteristics of TSS-grown shallots in terms of numberof leaves, number of tillers, stem diameter, and number of bulbsacross different animal manure types in Ultisol soil. The combinationof chicken manure and no shading yielded the best plantcharacteristics in terms of number of leaves, number of tillers, freshweight, and dry weight in Ultisol soil. The application of chickenmanure showed superior performance in number of tillers, stemdiameter, and fresh weight.